Mother Tongue versus English as a Second Language in Mathematical Word Problems: Implications to Language Policy Development in the Philippines : Implications to Language Policy Development in the Philippines - BAUTISTA, JUDY; Samonte, Ilynne; Improgo, Cecille Marie; Gutierrez, Merry Ruth (International Journal of Language and Literary Studies, 2020)
This study investigated the performance of 150 Tagalog and 131 Sinugbuanong Bisaya grade three pupils with regard to solving mathematical word problems written in their mother-tongue (L1) and in English as their second language (L2). The respondents were subjected to a validated teacher-made parallel tests based on the competencies stipulated in the first and second quarter mathematics curriculum guide of the Philippines. Results of which were compared and analyzed using two-tailed t-test. Findings show that the Tagalog pupils performed better in their mother-tongue over English as their second language. On the other hand, Sinugbuanong Bisaya pupils performed better in English as their second language over their mother-tongue. While results appear contradictory, contextual discussions offer valuable insights into the situation, allowing avenues for more exploration and investigations. As implication to language policy development, this study offers the use of translanguaging in content area instruction and assessment, specifically in the teaching and learning of mathematical problem solving